Kemajemukan Indonesia menurut ajaran Gereja Protestan Maluku dalam perpekstif teologi agama-agama - Theophillia Vristya Leatemia; Jhony Christian Ruhulessin; Ricardo Freedom Nanuru (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Plurality, including religious plurality in Indonesia, is an indisputable reality. Many conflicts based on religious plurality still occur in Indonesia today, and all religions in Indonesia must be responsible for them. This article aims to review the religious plurality concept as the face of Indonesia in the form of the Maluku Protestant Church??